Electrochemical decomposition of cyanides on tin dioxide electrodes in alkaline media - Fugivara, Cecilio Sadao [UNESP]; Sumodjo, PTA; Cardoso, Arnaldo Alves [UNESP]; Benedetti, Assis Vicente [UNESP] (Royal Soc Chemistry, 1996)
The electrochemical oxidation of cyanide in alkaline media was studied at different pH levels on SnO2 doped with Sb supported on titanium, at 25 degrees C, the electrooxidation of CN- at constant current follows a first-order rate law with a half life of t(1/2) = 35 min on SnO2-SbOx electrodes and t(1/2) = 69 min on SnO2-SbOx-RuO2 electrodes, in K2SO4(aq), pH 12, the reaction rate increases with the applied current and tends to reach a plateau when j > 20 mA cm(-2), In the pH range 10-13.5 the reaction rate diminishes as pH is increased owing to an increasing competition between CN- and OH- ions for the electrode surface. Addition of chloride to the solution does not alter the rate law but increases the reaction rate, A mechanism is proposed to explain the observed behaviour.
Keywords: cyanide electrooxidation; tin dioxide doped electrodes; kinetic study of cyanide oxidation